Quality of maternal and newborn care around the time of childbirth for migrant versus nonmigrant women during the COVID-19 pandemic: Results of the IMAgiNE EURO study in 11 countries of the WHO European region - Costa, R (2022)
Objective: To describe the perception of quality of maternal and newborn care (QMNC) around the time of childbirth among migrant and nonmigrant women in Europe. Methods: Women who gave birth at a health facility in 11 countries of the WHO European Region from March 2020 to July 2021 were invited to answer an online questionnaire including demographics and childbirth experience. Data were analyzed and compared for 1781 migrant and 20 653 nonmigrant women. Results: Migrant women who experienced labor perceived slightly more difficulties in attending routine antenatal visits (41.2% vs 39.4%; P = 0.001), more barriers in accessing facilities (32.9% vs 29.9%; P = 0.001), lack of timely care (14.7% vs 13.0%; P = 0.025), inadequate room comfort and equipment (9.2% vs 8.5%; P = 0.004), inadequate number of women per room (9.4% vs 8.6%; P = 0.039), being prevented from staying with their baby as they wished (7.8% vs 6.9%; P = 0.011), or suffering abuse (14.5% vs 12.7%; P = 0.022) compared with nonmigrant women. For women who had a prelabor cesarean, migrant women were more likely not to receive pain relief after birth (16.8% vs.13.5%; P = 0.039) and less likely to provide informal payment (1.8% vs 4.4%; P = 0.005) compared with nonmigrant women. Overall, the QMNC index was not significantly different for migrant compared with nonmigrant women. Conclusion: Gaps in overall QMNC were reported by both migrant and nonmigrant women, with improvements to healthcare necessary for all. © 2022 The Authors. International Journal of Gynecology & Obstetrics published by John Wiley & Sons Ltd on behalf of International Federation of Gynecology and Obstetrics.